Методологічні аспекти застосування методу групового урахування аргументів для прогнозування якості друкарських форм інтагліодруку - Киричок, Т. Ю.; Коротенко, О. В.; Коротенко, В. В. (ТОВ «Видавництво Ліра-К», 2025)
The paper explores the methodological principles of applying the group consideration of arguments method to develop a mathematical model for predicting the qualitative characteristics of intaglio printing plates.
Keywords: друкарська форма; інтагліодрук